Bimbingan Teknis Pengolahan Makanan Bagi Wirausaha Pemula Di Kabupaten Bireuen - Diah, Muhammad; Firmansyah, Deni; Murniyanti, Sri; Ernalis, Fitri (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The food processing business is an easy business and is suitable for beginner business people because the food processing business does not require very large capital, and can be done by beginners. This community service activity is carried out in 3 stages, namely the initial data collection stage, knowledge transfer stage, and follow-up evaluation. This activity provides new knowledge and understanding for beginners about doing business by utilizing local resources in Bireuen Regency